1974
DOI: 10.1111/j.1360-0443.1974.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Alcohol Withdrawal Syndrome: Findings and Problems

Abstract: Summary The acute alcohol withdrawal syndrome includes a whole serifs of gastrointestinal, cardiovascular, autonomic, neurological and psychic symptoms. In this study delirium tremens is regarded as the most severe stage of the withdrawal syndrome. In a study of 184 alcoholics (112 with delirium tremens) in which 14 symptoms of the types mentioned above were considered, a general syndrome was identified which could be divided into somatic and psychic subsyndromes. There were significant differences in the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
2
13
0
2
Order By: Relevance
“…The findings regarding the sleep alterations in the sample are in accordance with the ones in other studies, 7,20 in which the prevalence of insomnia in alcoholics ranges between 36% and 61%; in our study sleep efficiency, the most objective marker of insomnia, was disrupted in 56.8% (33/58) of the interviewees. When analyzing sleep efficiency in women, 46% (6/13) reported it being altered as compared to 60% (27/45) of men, being this in accordance with the literature.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The findings regarding the sleep alterations in the sample are in accordance with the ones in other studies, 7,20 in which the prevalence of insomnia in alcoholics ranges between 36% and 61%; in our study sleep efficiency, the most objective marker of insomnia, was disrupted in 56.8% (33/58) of the interviewees. When analyzing sleep efficiency in women, 46% (6/13) reported it being altered as compared to 60% (27/45) of men, being this in accordance with the literature.…”
Section: Discussionsupporting
confidence: 80%
“…10 The report of a lower proportion of alteration in sleep efficiency in women can be explained by their higher consumption of non specified hypnotics. 17,20 Anxious and depressive symptoms were reported by most interviewees, and the presence of these symptoms per se can produce sleep alterations, but alcohol consumption also produces both alterations and worsens sleep problems. 21 In the sample as well as in the general population, there is a tendency of women having a higher consumption of hypnotics, 69%, (9/13), as compared to 25% (12/45) of men, although the bad quality of sleep was present in both genders, 83% (37/45) among men and 100% (13/13) among women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baekeland et al (4) reported that 36% of 294 alcoholic outpatients had high scores on sleep disturbance as measured by a clinic physician. Similarly, Feuerlein (5) reported that 37% of 184 inpatients and outpatients with alcoholism had "sleep disturbance" as determined by a semistandardized interview. Caetano et al (6) investigated insomnia as a withdrawal symptom and found a 42% rate among 445 people referred to educational programs for driving under the influence, and a 67% rate among 748 men admitted to detoxification and residential treatment centers.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of insomnia and its self-medication with alcohol has not been investigated simultaneously in alcoholic samples (4)(5)(6). Nevertheless, other studies provide useful frequency estimates of self-medication.…”
Section: Introductionmentioning
confidence: 99%